Spatially Confined Functionalization of Transparent NiO Thin Films with a Luminescent (1, 10‐Phenanthroline)tris(2‐thenoyltrifluoroacetonato)europium Monolayer. Issue 7 (12th September 2014) - Smecca, Emanuele; Tudisco, Cristina; Giuffrida, Antonino E.; Catalano, Maria R.; Speghini, Adolfo; Malandrino, Graziella; Condorelli, Guglielmo G.
Abstract: Transparent MOCVD‐grown NiO films have been functionalized with the luminescent (1, 10‐phenanthroline)tris(2‐thenoyltrifluoroacetonato)europium(III) complex [Eu(TTA)3 phen] by combining sputter activation with a solution synthetic route. To introduce the Eu complex only on selected regions, some areas of the NiO surface were activated by Ar + ion sputtering and then functionalized with 3‐phosphonopropionic acid (CPPA) followed by the anchoring of Eu(TTA)3 phen through a ligand‐exchange reaction between β‐diketonato ligands and the carboxylic groups of CPPA. The functionalized material was characterized by X‐ray photoelectron, UV/Vis and luminescence spectroscopy. XPS measurements indicated that CPPA prefunctionalization and, in turn, the Eu(TTA)3 phen anchoring occurs only on the sputter‐activated region, while no anchoring takes place on the unactivated surface. The optical properties of the Eu(TTA)3 phen–NiO system were evaluated by UV/Vis and luminescence spectroscopy. Abstract : Anchoring of the Eu(TTA)3 phen complex on MOCVD‐grown NiO films is reported. The NiO surface was activated by means of a sputtering process and functionalized with a phosphonic linker, followed by the coordination of the Eu complex through a ligand‐exchange reaction. The luminescent hybrid system has been proven to retain the optical properties of the Eu complex.